PERSEPSI REMAJA TERHADAP KESEHATAN MENTAL - Kiki Rizki Aulia (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2025)
Mental health is a crucial aspect of early adolescent development, particularly among junior high school students. During this transitional stage, students face emotional, social, and academic changes that may affect their psychological well-being. This study aimed to explore junior high school students’ perceptions of mental health and the factors shaping these perceptions. A qualitative descriptive approach was employed, involving students aged 12–15 years selected through purposive sampling. Data were collected via in-depth interviews and analyzed using thematic analysis. The findings indicated that students perceived mental health as positive emotional states, emotional regulation abilities, and comfort in peer and school interactions. These perceptions were influenced by academic demands, peer relationships, family support, and exposure to social media. However, limited understanding and early stigma were also identified, leading some students to hesitate in expressing their emotions or seeking help. This study concludes that students’ perceptions of mental health are context-dependent and reflect early adolescent developmental characteristics, highlighting the need for developmentally appropriate mental health psychoeducation in junior high schools.